DETEKSI ANTIBODI MULTIPEL HEPATITIS C DALAM DARAH DONOR (Multiple Antibody Detection of Hepatitis C in Donor Blood) - Ranti Permatasari; Aryati Aryati; Budi Arifah (Indonesian Association of Clinical Pathologist and Medical laboratory, 2015)
Hepatitis C (HCV) infection could be spread by blood transfusion. Screening of HCV in donor blood could prevent HCV infection to therecipient. HCV antibody test using rapid test of multiple antibody detection by immunochromatography method is an easy and rapid testthat could detect four HCV antibodies separately. The aim of this study was to evaluate the diagnostic value of antibody HCV using multipleantibody detection rapid test in diagnosing HCV infection. This was an analytical observational study with a cross sectional design. Thesamples consisted of 42 donors’ blood serum from the Surabaya Branch of the Indonesian Red Cross which underwent HCV infectiontest using ELISA method. The samples were then tested using PCR HCV RNA as the gold standard and antibody HCV multiple antibodydetection rapid test The diagnostic value of HCV antibody test using multiple antibody detection rapid test by immunochromatographymethod showed a diagnostic sensitivity of 100%, diagnostic specificity of 75%, positive predictive value of 66.7% and negative predictivevalue of 100%, a diagnostic efficiency of 83.3%, with a positive probability ratio of 4 times. The most often positive antibody patternwas four (4) positive antibodies (core protein, NS3, NS4 and NS5). Core protein (CP) and NS3 were the most often positive antibodies.Based on this study result, the HCV antibody test using multiple antibody detection rapid test by immunochromatography method hasa good diagnostic value.